Distinguishing the contributions of natural ecosystems and water infrastructures to water provisioning services at watershed scale - Jian Zhang; Jian Zhang; Shidong Zhang; Shidong Zhang; Yuan Huang; Feifei Fan; Jinfeng Ma; Hua Zheng; Hua Zheng (Frontiers in Earth Science)
Natural ecosystems and water infrastructure (such as reservoirs) jointly exert an influence water flow by means of retaining, regulating, storing, and releasing water, thereby enhancing the availability of water resources to satisfy human demands. Previous research has predominantly concentrated on the role of natural ecosystems in water provision services; however, studies that integrate the contributions of both natural ecosystems and infrastructure to quantify their respective impacts on water provisioning services remain scarce. Here we utilize the SWAT hydrological model to simulate the spatiotemporal dynamics of water provisioning services in the Qinling-Danjiang watershed—an area prone to seasonal water shortages. The study delineates the supply and beneficiary areas, quantifying the relative contributions of natural ecosystems and infrastructure to watershed water provisioning services and their ecosystem service values were respectively evaluated by delineating the supply and beneficiary areas of water provisioning services and using scenario analyses. The annual water provision in the Danjiang watershed was 2.394 × 103 million m3, with significant variation across watershed and months. The total water demand from stakeholders was 1.122 × 103 million m3, with agricultural irrigation being the largest consumer, and 52.81% of the area experiencing a supply deficit. Under the baseline scenario, the value of water provisioning services was 14.602 billion CNY. In a scenario without reservoir infrastructure, water provision of natural ecosystems increased by approximately 27% to 3.039 × 103 million m3 (about 18.538 billion CNY), but exacerbated seasonal imbalances. Conversely, in a scenario without natural ecosystems, the water provision of reservoir infrastructure dropped by over 90% to 193 million m3 (about 1.179 billion CNY), which was insufficient to meet regional demands. This study provides a novel perspective for understanding the interactions between natural ecosystems and infrastructure in water provisioning services and offers a new approach to distinguish their relative contribution in water provisioning services, which is of great significance for accounting nature’s contribution to people.